2018
DOI: 10.7573/dic.212510
|View full text |Cite
|
Sign up to set email alerts
|

Needs and preferences of women users of oral contraceptives in selected countries in Central and Eastern Europe

Abstract: BackgroundThe availability of various oral contraceptive (OC) pill formulations with different hormone compositions suggests that there is potential to align a particular product with an individual user’s needs and preferences. To explore this concept further, a survey was conducted of current users of OCs to define and confirm areas of specific needs, and to gain insight into their views and preferences for OC formulations.MethodsDuring November and December 2015, women users (n=615) of OCs in five Central an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In terms of study generalizability, a low-dose EE (20 μg)containing OC was utilized, which is reflective of current practice, as women tend to prefer lower doses because of concerns of the side effects of exogenous hormones on their bodies. 15,16 Commonly prescribed OCs contain EE in ranges from 20 to 35 μg with many options available at the lower dose range. Thus, the significance of this study is that it showed that low doses of EE did not result in ALT elevations and therefore drug-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of study generalizability, a low-dose EE (20 μg)containing OC was utilized, which is reflective of current practice, as women tend to prefer lower doses because of concerns of the side effects of exogenous hormones on their bodies. 15,16 Commonly prescribed OCs contain EE in ranges from 20 to 35 μg with many options available at the lower dose range. Thus, the significance of this study is that it showed that low doses of EE did not result in ALT elevations and therefore drug-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 27 studies were evaluated using the Cochrane Risk of Bias tool; 3 studies were considered as low risk of bias, 39,42,44 9 studies were considered as some concerns, 46,47,49,50,55,56,58,59 and 15 studies at high risk. 29,30,33,[35][36][37]41,48,51,52,54,57,60,61 Most studies that were classified as some concerns exhibited deficits in the randomization process while most studies that were classified as high risk demonstrated concerns in the missing outcome data domain.…”
Section: Risk Of Bias and Quality Of The Assessed Studiesmentioning
confidence: 99%
“…Regarding informational communication, studies in several countries indicate that information and knowledge about side effects and effectiveness are fundamental when women choose contraceptives [25,65,68,[74][75][76][77], including at the time of an abortion [15,72,73].…”
Section: Contraceptive Counselling At the Time Of An Abortionmentioning
confidence: 99%
“…Information regarding side effect also seems to be central in counselling since it is common for women to discontinue contraceptive use due to experiences and fear of side effects [25,68,69]. Side effects that trouble women are effects on mood [70], weight gain, and changes in menstrual patterns [76]. Fear of side effects seems to also negatively influence women's contraceptive use after an abortion [79][80][81].…”
Section: Informational Communication Concerning Effectiveness and Sidmentioning
confidence: 99%